2022
DOI: 10.3390/ijerph19084554
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Ethical Climate and Job Satisfaction among Nurses: A Scoping Review

Abstract: The aim of this study was to map and summarize the published research findings on hospital ethical climate and its relationship with nursing staff job satisfaction as well as strategies proposed in the literature for the improvement of hospital ethical climate and job satisfaction through the actions of nursing staff in leadership positions. A scoping review has been performed in accordance with the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension scoping reviews state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
4
18
0
2
Order By: Relevance
“…Prior research has established a strong relationship between ethical climate and nurses' job satisfaction. 24 It accords with both recent 34 and the present findings that link ethical climate perceptions with intention to leave. When comparing those who considered…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Prior research has established a strong relationship between ethical climate and nurses' job satisfaction. 24 It accords with both recent 34 and the present findings that link ethical climate perceptions with intention to leave. When comparing those who considered…”
Section: Discussionsupporting
confidence: 91%
“…Prior research has reported positive perceptions of ethical climate in pediatric settings. 23 Ozdoba et al 24 described, in a scoping review, that the role of a manager is essential in creating and fostering an ethical climate. However, in this study, relations to patients and coworkers were appreciated even more, and contributed most to the high overall scores.…”
Section: Discussionmentioning
confidence: 99%
“…La hipótesis 6 (Rho=0,47; p=0,00), tuvo como resultado una correlación moderada en los incentivos que generan de manera positiva al desempeño laboral. Para Ozdoba et al, (2022) los incentivos permite a las organizaciones de servicios públicos a mantener y atraer de mejor manera el talento dentro del mercado, sin duda es uno de los mejores motivos del porque los trabajadores deciden porque quedarse en la organización. Por otro lado, generalmente los incentivos es una forma de como recompensar y motivar a los trabajadores en el desempeño de la fuerza laboral (Chiang M. et al, 2021).…”
Section: Discussionunclassified
“…El clima organizacional es uno de los elementos importantes en el desarrollo de las organizaciones u empresas, ya que implica en el desenvolvimiento de los colaboradores para una correcta ejecución de actividades y procesos (Prasad et al, 2020). El comprender como afecta el clima organización en la satisfacción laboral de los trabajadores, se refleja a través de una alta rotación de personal por causa de incumplimiento de políticas corporativas, así como también, incertidumbres y desmotivación donde no existe una retroalimentación del desempeño por parte de los jefes en sus áreas de trabajo (Ozdoba et al, 2022). Es por ello que, actualmente la satisfacción laboral es uno de los puntos clave en una organización pública y privada, debido a que un personal laboral totalmente satisfecho alcanza las metas establecidas por parte de la empresa, por lo contrario puede haber una variedad de factores que afecten un clima organizacional dentro de una empresa u organización, que es a través de un bajo rendimiento del personal laboral, desmotivación, descontento e incumplimiento de normar y directrices que forman parte de canales de comunicación dentro de la empresa (Sonarita et al, 2019).…”
Section: Introductionunclassified
“…The result of the research indicated a positive correlation among sub-dimensions of job satisfaction (professionalism, caring, rules, independence climate) and organisational commitment. in support" of thisa, Ozdoba, Dziurka, Pilewska-Kozak, and Dobrowolska [65] examine hospital ethical climate and job satisfaction among nurses. A total of 235 nurses participated in the study.…”
Section: Related Studiesmentioning
confidence: 99%